Determining the center of a keratoconus: Comparison of different tomographic parameters and impact of disease severity - Steinwender, Gernot; Kollenc, Alexander; Shajari, Mehdi; Sommer, Michael; Borenich, Andrea; Horwath-Winter, Jutta; Lindner, Ewald; Woltsche, Nora; List, Wolfgang; Wedrich, Andreas (Frontiers in Medicine, 2022)
Purpose There exists remarkable variation in definitions for the location of the center of a keratoconus. The objective of this study was to analyze deviations between locations obtained by different tomographic maps for that purpose. Furthermore, it was investigated whether these deviations are influenced by disease severity. Methods In 162 eyes with keratoconus, corneal tomographic maps derived by Scheimpflug technology were retrospectively analyzed to determine the cone location with 5 different methods: maximum axial curvature of the front surface (Kmax), maximum tangential curvature of the front surface (tKmax), minimum pachymetry (Pachymin), maximum elevation of the front surface (ELEF), and maximum elevation of the back surface (ELEB). Distances between the locations were calculated and tested for a correlation with keratoconus severity and distance between cone and corneal vertex. Results Cone locations derived from the curvature maps (Kmax, tKmax) showed the lowest agreement with the locations determined by pachymetry or elevation maps. The largest distances were found between Kmax and Pachymin [Median and Interquartile range: 1.19 mm (0.87, 1.60)], Kmax and ELEB [1.12 mm (0.79, 1.41)], and Kmax and ELEF [0.97 mm (0.64, 1.27)]. Low distances (<0.5 mm) were calculated between ELEB and ELEF, and ELEB and Pachymin. All of the calculated distances between the locations showed a significant negative correlation with keratoconus severity and most of them increased significantly with a more peripheral position of the cone (p < 0.05). Conclusions There was low consistency between different methods for describing the location of a keratoconus. Curvature-based determinations of the cone center (Kmax, tKmax) showed the highest deviations and should not be used for that purpose. However, the discrepancies between different cone location methods diminished with increasing disease severity and more central position of the cone.